Incidental Finding of Pulmonary Embolism at Workup Before SIRT. (10th September 2021) - Kramer, Stine Jentoft; Amanavicius, Nerijus; Staanum, Peter Frøhlich; Villadsen, Gerda Elisabeth; Arveschoug, Anne Kirstine
Abstract: Selective internal radiation therapy (SIRT) is a catheter-guided treatment offered to selected patients with primary and secondary liver malignancies. SIRT is preceded by a workup procedure, where 99m Tc-MAA (macroaggregated albumin) is injected in the tumor supplying artery/arteries followed by MAA scintigraphy. SIRT is frequently offered to patients with hepatocellular carcinoma (HCC), but large HCCs are known to be associated with a high risk of liver-to-lung shunting. We present a HCC patient case where a large lung-shunt enabled diagnosis of pulmonary embolism.